A rare type of cancer in children: extranodal marginal zone B-cell (MALT) lymphoma of the ocular adnexa - İncesoy-Özdemir, Sonay; Yüksek, Nazmiye; Bozkurt, Ceyhun; Şahin, Gürses; Memiş, Leyla; Dizman, Ayşen; Ertem, Ulya (The Turkish Journal of Pediatrics, 2014)
Primary ocular adnexal mucosa-associated lymphoid tissue (MALT) lymphomas (OAMLs) are mostly seen in the 5th-7th decades of life, with female predominance, and they occur rarely in children. Thus, knowledge about this cancer type is obtained from adult data in the literature, while the data regarding OAMLs in the pediatric population are limited to a few case reports. Herein, we report a 10-year-old boy with OAML who was treated successfully with radiotherapy, and we discuss this uncommon lymphoma in children.